2020
DOI: 10.1002/ana.25731
|View full text |Cite|
|
Sign up to set email alerts
|

Extra‐Axial Inflammatory Signal in Parameninges in Migraine with Visual Aura

Abstract: Objective: Cortical spreading depression (CSD) underlies the neurobiology of migraine with aura (MWA). Animal studies reveal networks of microvessels linking brain-meninges-bone marrow. CSD activates the trigeminovascular system, evoking a meningeal inflammatory response. Accordingly, this study examines the upregulation of an inflammatory marker in extra-axial tissues in migraine with visual aura. Methods: We used simultaneously acquired 11 C-PBR28 positron emission tomography/magnetic resonance imaging data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 54 publications
4
56
0
Order By: Relevance
“…The occipital cerebral cortex tested in our study, is the common area for the development of CSD, a phenomenon underlying aura in the specific form of migraine with aura [ 58 ]. Accordingly, CSD is likely giving rise to multiple visual abnormalities at the initiation of migraine attacks [ 59 , 60 , 61 , 62 ]. Temporal, frontal cortical lobes and the cerebellum were also reported to be altered in chronic migraine patients during pain signaling events [ 63 , 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The occipital cerebral cortex tested in our study, is the common area for the development of CSD, a phenomenon underlying aura in the specific form of migraine with aura [ 58 ]. Accordingly, CSD is likely giving rise to multiple visual abnormalities at the initiation of migraine attacks [ 59 , 60 , 61 , 62 ]. Temporal, frontal cortical lobes and the cerebellum were also reported to be altered in chronic migraine patients during pain signaling events [ 63 , 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, PET imaging has shown that the migraine medication dihydoergotamine does not enter the brain, 14 and no gadolinium crosses into the CSF in dynamic contrast‐enhanced MRI in migraine; 15 conversely, BBB breakdown was demonstrated in hemiplegic migraine 16,17 . Recently, inflammation in the occipital cortex in migraine with visual aura was reported 18 . A leak has been inferred from nonspecific blood surrogates of the BBB 19 and in animal model studies 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…The human skull bone marrow contains numerous microvascular channels that serve in animals as conduits for inflammatory cell migration into the meninges and possibly to other intracranial structures related to headache, 3 as documented in experimental stroke and chemical meningitis. Interestingly, most nerve fibers in the bone marrow are nociceptive and CGRP‐containing 9 . The same study also reported that CGRP is involved in mobilization of myeloid cells from the bone marrow 9 .…”
mentioning
confidence: 78%
“…Interestingly, most nerve fibers in the bone marrow are nociceptive and CGRP‐containing 9 . The same study also reported that CGRP is involved in mobilization of myeloid cells from the bone marrow 9 . It could therefore be speculated that calvarial bone marrow provides a source of inflammatory cells and proinflammatory molecules in meninges and overlying bone following trauma to the calvarium.…”
mentioning
confidence: 94%